Representations of Maghrebians' Immigrant Life in France in Two Literary Generations: A Multilevel Cognitive Stylistic Reading of Driss Chraibi’s Les boucs and Azouz Begag’s Le gone du Chaaba - Khalid Majhad (Yayasan Visi Intan Permata, 2020)
While political analysts, economists, cultural studies scholars have all been offering insightful analyses of the different matters relating to immigrant life in different parts of the world, this article reaches for a first-hand testimony in two autobiographical novels by two internationally recognized Maghrebian novelists who respectively represent the first and second generations of Maghrebian immigrants in France. In a rather innovative manner, the portrayal of immigrant life in the two novels is analyzed from a cognitive stylistic perspective, and informed by the author’s multiple research viewpoints, those of a Maghrebian literature critic, a francophone postcolonial studies researcher and a frequent visitor to France carrying the concerns of an extended family based there. The interest in style during our close reading of these largely autobiographical narratives is based on the assumption that an author's style is a reflection of their attitude and worldview. Chraibi’s novel Les Boucs (1955) is as timely now as it was in the day of its first appearance for its balanced and largely objective analysis of the sociological, psychological and economic conditions of North African immigrants. Stylistically, Les boucs features a close correlation between its form and content in that the chaotic nature of immigrant life is formally embodied in Chraibi's non-linear mode of writing. In contrast to the bleak picture presented throughout Chraibi's text, Begag's convivial approach oozes hope for his readers who come to realize the futility of continuing to curse the state of deprivation and inequity while there can always be ways setbacks can be turned into opportunities. The study uses a qualitative method of stylistic analysis and applies the two necessary principles of 'contextualization' and 'comprehensiveness' to ensure a high degree of analytical and interpretive validity.